Prediction of subsurface damage depth of ground brittle materials by surface profiling. (7th March 2007) - Ohta, Tsutomu; Yan, Jiwang; Kuriyagawa, Tsunemoto; Kodera, Sunao; , Tomoaki Nakasuji
In the manufacturing of infrared optics, grinding is usually used as a premachining process for generating aspherical lens figures on brittle materials such as germanium and silicon before diamond turning or polishing. However, microcracks will be generated in workpiece materials by the grinding process. The subsurface crack depth determines the depth of material removal of the finishing processes and affects the total manufacturing time. In order to minimise the depth of finishing removal, it is important to know the grinding-induced crack depth accurately. In this paper, we attempt to predict the subsurface damage depth by surface profiling techniques. The surface roughness of ground silicon and germanium was measured by a stylus-type profilometer with different stylus geometries and the subsurface crack depth was evaluated using two different methods, namely, small-tool polishing method and slanted-polishing method. The relationship between the surface roughness and the subsurface crack depth was experimentally investigated.